Improving parenting skills to prevent negative discipline in children: A scoping review - Nafisah, Khilda Durrotun; Rokhmah, Islamiyatur; Astuti, Andari Wuri; Kit, Ayano (Universitas 'Aisyiyah Yogyakarta, 2025)
Introduction: Negative discipline is a violation of children's rights to respect for their physical integrity and human dignity, health, development, education and protection from violence. For children, negative discipline can increase the risk of bad outcomes, namely problematic social and parental relationships, weak moral internalization, stress responses, and mental health problems. Purpose: This study aims to improve parenting skills to prevent negative discipline in children. Method: This scoping review aims to identify the latest scientific evidence related to negative discipline in children. The article search used relevant databases such as PubMed, ScienceDirect, and Wiley Online Library. The article search obtained 11 articles for further analysis. The analysis was based on the Joanna Briggs Institute (JBI). The search used some keywords, namely Parenting* OR Parenting style* OR Child Rearing* AND discipline* OR harsh discipline* OR punitive violence* OR Corporal punishment* OR physical punishment*. The author used filters, namely articles published in English, articles published from 2019-2023; and articles about parenting skills to prevent negative discipline in children. Conclusion: Negative discipline can cause psychological problems in children. Children who frequently get negative discipline will experience anxiety. In addition, negative discipline can disrupt children's emotional development causing aggressive behavior and disrupting mental health.